Success of firm strategies in e-commerce - Franz Hackl; Michael Hölzl-Leitner; Rudolf Winter-Ebmer; Christine Zulehner (Johannes Kepler University of Linz, Department of Economics, 2018)
The choice of an appropriate e-commerce strategy is crucial for the survival of online stores in B2C e-commerce business. We use a comprehensive data set from the Austrian price search engine geizhals.at to identify successful e-commerce strategies. An e-commerce strategy is a set of choices including the listing decision, availability decision, and decisions on price and shipping cost. We apply cluster analysis to identify the different strategies that have been used by online retailers. Using various success measures such as revenue, clicks, market share, and the survival of firms, as dependent variables in our regression analyses, we present empirical evidence on the effectiveness of different e-commerce strategies.
Keywords: L81; L10; 330; e-commerce; online trade; business strategies; retailing